EFFECT OF BROILER DIET COMPOSITION ON NEWCASTLE DISEASE ANTIBODY PRODUCTION - A. M. Saeed Al Saigh (Mesopotamia Journal of Agriculture)
An experiment was conducted at the college of veterinary medicine to investigate the effect of two types of broiler starter diets, with or without animal protein, on Newcastle disease antibody production. Bursal weight index was also studied. Two replicates with 10 male broiler chicks, each were used in each treatment groups, A and B, for a total of 40 birds .The experimental birds were reared from day old till 4 weeks of age. Results revealed that there were no significant effects on antibody titer and bursal weight index, due to different types of the experimental diets. It was found that out of antibody titers 20 and 40, only 3 and 2 birds were found to be positive, respectively .Where as out of antibody titers 80 and 160 only 3 birds from each group, A and B, where found to be positive verses 8 and 4 birds from group B were shown to be positive.